2022
DOI: 10.3389/fviro.2022.926831
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of innate immune response to hepatitis B virus genotype F acute infection in tree shrew (Tupaia belangeri) model

Abstract: Hepatitis B virus (HBV) infection is a global public health problem. The clinical outcomes of HBV infections are influenced by host as well as viral factors, including viral genotypes and subgenotypes. The interplay between HBV and host innate immunity remains unclear because of the lack of a suitable small animal model. Tree shrews (Tupaia belangeri) have been utilized as a useful animal model for hepatitis viruses such as hepatitis B and C viruses. In this study, we characterized acute infections by HBV geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 71 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…These cells can either promote infection upon TLR engagement or produce proinflammatory cytokines and chemokines to aid in removing the virus. By generating antimicrobial molecules like TNF-α and IFN, PAMP/microbe-associated molecular patterns (MAMPs)-induced activation of TLR signaling reduces the replication and spread of invading pathogens/microbes ( 38 , 39 ). When HBV infection occurs, the TLR response may alter HBV-specific T and B cell responses, ending the HBV infection ( 23 , 40 ).…”
Section: Tlr Response To Hbv Infection In Humanmentioning
confidence: 99%
See 3 more Smart Citations
“…These cells can either promote infection upon TLR engagement or produce proinflammatory cytokines and chemokines to aid in removing the virus. By generating antimicrobial molecules like TNF-α and IFN, PAMP/microbe-associated molecular patterns (MAMPs)-induced activation of TLR signaling reduces the replication and spread of invading pathogens/microbes ( 38 , 39 ). When HBV infection occurs, the TLR response may alter HBV-specific T and B cell responses, ending the HBV infection ( 23 , 40 ).…”
Section: Tlr Response To Hbv Infection In Humanmentioning
confidence: 99%
“…Tree shrews’ whole genomes have shown that they are more closely linked to humans than to rodents ( 54 ). Numerous studies have indicated that tree shrews are vulnerable to HBV infection ( 39 ). In research, Kayesh et al.…”
Section: Tlr Response To Hbv Infection In Humanmentioning
confidence: 99%
See 2 more Smart Citations
“…It serves as a model for studying HBV and has been used to simulate acute and chronic HBV infection, showing similar liver histopathological changes and hepatocellular carcinoma features as seen in HBV patients. Whole genome sequencing has revealed that tupaia is genetically similar to primates and falls between humans and rodents. , Infections in adult animals are typically mild and transient, but in newborn animals, they can lead to long-term liver immunopathological alterations, such as fibrosis formation, hepatocellular cancer, and persistent infection with moderate viremia. , In particular, this model can be used to imitate immunoactive infection and have been utilized as models for viral hepatitis, providing insights into the direct impact of HBV infection on liver gene expression …”
Section: Infection and Replication System Of Hbvmentioning
confidence: 99%